Frequency and Antibiotic Sensitivity Pattern of Culture Positive Salmonella Typhi in Children Visiting to RHQ Hospital Gilgit - Ali, Muneera; Khan, Ziaullah; Bari, Abdul (Journal of Fatima Jinnah Medical University, 2024)
Background: Typhoid fever, caused by Salmonella enterica serovar typhi, is a common infection that affects multiple body systems. Salmonella is a constantly evolving and adaptable bacterium, so overuse of a particular treatment may eventually lead to the development of resistance. To determine the frequency and antibiotic sensitivity pattern of culture positive salmonella typhi in children visiting to RHQ hospital Gilgit. Patient and Methods: An observational cross-sectional study was conducted at RHQ Hospital Gilgit from June to August 2022. Through non-probability, consecutive sampling, a total of 150 patients of either gender with ages ranging from 1 month to 12 years and enteric fever symptoms as well as positive blood culture results for Salmonella species were enrolled in this study. In the microbiology lab, the blood culture bottles were incubated for seven days at 37 °C while daily growth indicators were monitored. On the pre-designed proforma, the basic demographic history and Salmonella species' susceptibility patterns were noted. Data was entered and analyzed by SPSS 25.0. Results: The average age of these patients was 6.63+3.35 years. Among the patients, the majority were male, accounting for 97 individuals (64.6%), while 53 individuals (35.4%) were female. Fever was most common symptoms among patients with highest frequency of 59, followed by body aches (35). Almost 98% of cases were resistant to ciprofloxacin, commonly used as a first-line drug against Salmonella Typhi in Pakistan. Resistance was also very high against ampicillin (92%). The Azithromycin and Imipenem were the only drugs with a sensitivity of more than 90%. Conclusion: The existence of typhoid fever cases and the increasing resistance of Salmonella strains to ceftriaxone and Ampicillin are causes for serious concern. Meropenem and azithromycin, whether used individually or in combination, proved to be the most effective antibiotics for treatment.